-2(x-4)+6=3

Simple and best practice solution for -2(x-4)+6=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(x-4)+6=3 equation:


Simplifying
-2(x + -4) + 6 = 3

Reorder the terms:
-2(-4 + x) + 6 = 3
(-4 * -2 + x * -2) + 6 = 3
(8 + -2x) + 6 = 3

Reorder the terms:
8 + 6 + -2x = 3

Combine like terms: 8 + 6 = 14
14 + -2x = 3

Solving
14 + -2x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-14' to each side of the equation.
14 + -14 + -2x = 3 + -14

Combine like terms: 14 + -14 = 0
0 + -2x = 3 + -14
-2x = 3 + -14

Combine like terms: 3 + -14 = -11
-2x = -11

Divide each side by '-2'.
x = 5.5

Simplifying
x = 5.5

See similar equations:

| (7v+3v+6)+(-4v+2v+1)= | | 5(2a-4b)-4(a-5b)= | | 7x+168+4x+166=180 | | logx(27)=10 | | 9a(-7a+4)= | | 5y^4+3y^4= | | 3u-10=14 | | 4+(x-5)=2(3-x) | | 4x^2-28x+c= | | Z+20=6 | | (Xy^2)(x^2+3xy+9)=0 | | 2x^8+6x^8= | | 2(x+6)x^2=90 | | 21x^2y+2xy-8=0 | | 3(x-2)=5(2+3) | | h+h+4=218 | | y=x^5+6x+8 | | 14(y-7)+12y=16-70 | | 6+2(7x+2)=3 | | 5y=4x+12 | | -3x+3=5x-5 | | (3a+4b)(3a-4b)= | | x*1+3*1,5+(x-3)*2=19,5 | | 3x+37=97 | | x^2-4x+2=-1 | | X=15000+0.36(8600+0.2X) | | h+h+20=300 | | 3-(x-4)=4-(2x+5) | | 15-(-23)= | | 0=-x^2-9x+7 | | 28u^2-27u-10=0 | | .06(z-300)+.05z=.70z-205 |

Equations solver categories